RNA Sequencing Reveals Alterations and Similarities in Cell Metabolism, Hypoxia and Immune Evasion in Primary Cell Cultures of Clear Cell Renal Cell Carcinoma - Simon, Adrian Georg; Esser, Laura Kristin; Ellinger, Jörg; Ritter, Manuel; Kristiansen, Glen; Muders, Michael H.; Mayr, Thomas; Toma, Marieta Ioana (Frontiers in Oncology, 2022)
The treatment of advanced renal cell carcinoma remains a challenge. To develop novel therapeutic approaches, primary cell cultures as an in vitro model are considered more representative than commercial cell lines. In this study, we analyzed the gene expression of previously established primary cell cultures of clear cell renal cell carcinoma by bulk (3’m)RNA sequencing and compared it to the tissue of origin. The objectives were the identification of dysregulated pathways under cell culture conditions. Furthermore, we assessed the suitability of primary cell cultures for studying crucial biological pathways, including hypoxia, growth receptor signaling and immune evasion. RNA sequencing of primary cell cultures of renal cell carcinoma and a following Enrichr database analysis revealed multiple dysregulated pathways under cell culture conditions. 444 genes were significantly upregulated and 888 genes downregulated compared to the tissue of origin. The upregulated genes are crucial in DNA repair, cell cycle, hypoxia and metabolic shift towards aerobic glycolysis. A downregulation was observed for genes involved in pathways of immune cell differentiation and cell adhesion. We furthermore observed that 7275 genes have a similar mRNA expression in cell cultures and in tumor tissue, including genes involved in the immune checkpoint signaling or in pathways responsible for tyrosine kinase receptor resistance. Our findings confirm that primary cell cultures are a representative tool for specified experimental approaches. The results presented in this study give further valuable insights into the complex adaptation of patient-derived cells to a new microenvironment, hypoxia and other cell culture conditions, which are often neglected in daily research, and allow new translational and therapeutic approaches.e often neglected in daily research, and allow new translational and therapeutic approaches.